Alzheimer's disease as an autoimmune disorder of innate immunity endogenously modulated by tryptophan metabolites. Issue 1 (6th April 2022) - Meier‐Stephenson, Felix S.; Meier‐Stephenson, Vanessa C.; Carter, Michael D.; Meek, Autumn R.; Wang, Yanfei; Pan, Luzhe; Chen, Qiangwei; Jacobo, Sheila; Wu, Fan; Lu, Erhu; Simms, Gordon A.; Fisher, Laural; et al.
Abstract: Introduction: Alzheimer's disease (AD) is characterized by neurotoxic immuno‐inflammation concomitant with cytotoxic oligomerization of amyloid beta (Aβ) and tau, culminating in concurrent, interdependent immunopathic and proteopathic pathogeneses. Methods: We performed a comprehensive series of in silico, in vitro, and in vivo studies explicitly evaluating the atomistic–molecular mechanisms of cytokine‐mediated and Aβ‐mediated neurotoxicities in AD.  Next, 471 new chemical entities were designed and synthesized to probe the pathways identified by these molecular mechanism studies and to provide prototypic starting points in the development of small‐molecule therapeutics for AD.   Results: In response to various stimuli (e.g., infection, trauma, ischemia, air pollution, depression), Aβ is released as an early responder immunopeptide triggering an innate immunity cascade in which Aβ exhibits both immunomodulatory and antimicrobial properties (whether bacteria are present, or not), resulting in a misdirected attack upon "self" neurons, arising from analogous electronegative surface topologies between neurons and bacteria, and rendering them similarly susceptible to membrane‐penetrating attack by antimicrobial peptides (AMPs) such as Aβ. After this self‐attack, the resulting necrotic (but not apoptotic) neuronal breakdown products diffuse to adjacent neurons eliciting further release of Aβ, leading to a chronic self‐perpetuating autoimmune cycle.  AD thus emerges as a brain‐centric autoimmune disorder of innate immunity. Based upon the hypothesis that autoimmune processes are susceptible to endogenous regulatory processes, a subsequent comprehensive screening program of 1137 small molecules normally present in human brain identified tryptophan metabolism as a regulator of brain innate immunity and a source of potential endogenous anti‐AD molecules capable of chemical modification into multi‐site therapeutic modulators targeting AD's complex immunopathic–proteopathic pathogenesis.  Discussion:  Conceptualizing AD as an autoimmune disease, identifying endogenous regulators of this autoimmunity, and designing small molecule drug‐like analogues of these endogenous regulators represents a novel therapeutic approach for AD.